1984
DOI: 10.3189/s0022143000008467
|View full text |Cite
|
Sign up to set email alerts
|

Solute Acquisition in Glacial Melt Waters. I. Fjallsjökull (South-East Iceland): Bulk Melt Waters with Closed-System Characteristics

Abstract: Variations in dissolved cations, total alkalinity, sulphate, and field pH are recorded for samples of precipitation, supraglacial melt, and bulk melt waters (those emerging at the portal) from Fjallsjökull (south-east Iceland). The composition of supraglacial melt indicates derivation from precipitation by the acquisition of solutes from the weathering and dissolution of rock debris, in a system open to atmospheric carbon dioxide. Bulk melt waters have variable compositions, approaching saturation with calcite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 12 publications
(25 reference statements)
1
36
0
Order By: Relevance
“…Calcite dissolution from basaltic weathering has been reported to exert significant influence on glacier hydrochemistry (Raiswell and Thomas, 1984;Fairchild et al, 1999b), thus it is important to emphasize that no trace carbonates have been identified (detection limit is c. 0.2%), either in the pristine rock, the sediment deposits or the suspended sediment in the bulk meltwater.…”
Section: Geological Settingmentioning
confidence: 98%
“…Calcite dissolution from basaltic weathering has been reported to exert significant influence on glacier hydrochemistry (Raiswell and Thomas, 1984;Fairchild et al, 1999b), thus it is important to emphasize that no trace carbonates have been identified (detection limit is c. 0.2%), either in the pristine rock, the sediment deposits or the suspended sediment in the bulk meltwater.…”
Section: Geological Settingmentioning
confidence: 98%
“…Disko, Greenland [ Yde et al ., ], Rhone Glacier, Switzerland [ Hosein et al ., ], South Cascade Glacier, USA [ Reynolds and Johnson , ], Gangorti, Himalaya [ Singh et al ., ], and Satopanth, Himalaya [ Singh and Hasnain , ], all have water chemistries that plot on both sides of the open system line. The chemistry of Fjallsjökull, Iceland [ Raiswell and Thomas , ], diverges substantially from the open system line, implying closed system depletion of CO 2 . But its high alkalinity suggests substantial open system behavior occurred before closure.…”
Section: Comparison To Published Datamentioning
confidence: 99%
“…12, 1825±1849 (1998) Mean ratios of * Ca 2 : * Mg 2 and Na : Cl 7 have been determined for bulk, upwelling and conduit meltwaters and are presented in Table IV. The pCO 2 signature of a solution re¯ects the rate at which CO 2 diuses into or out of solution relative to the rate of other chemical weathering reactions (Raiswell, 1984;Raiswell and Thomas, 1984;Thomas and Raiswell, 1984). The so called``sulfate mass fraction'' (SMF) of meltwater samples has also been derived in the following manner: Table IV.…”
Section: Solute Output Hydrochemistrymentioning
confidence: 99%